(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article highlights the role of science and education in providing the agricultural sector with innovative human capital, as well as the priorities for creating favorable conditions for the entry of young professionals into the agricultural sector.